2015
DOI: 10.1038/srep10654
|View full text |Cite
|
Sign up to set email alerts
|

Economical analysis of saturation mutagenesis experiments

Abstract: Saturation mutagenesis is a powerful technique for engineering proteins, metabolic pathways and genomes. In spite of its numerous applications, creating high-quality saturation mutagenesis libraries remains a challenge, as various experimental parameters influence in a complex manner the resulting diversity. We explore from the economical perspective various aspects of saturation mutagenesis library preparation: We introduce a cheaper and faster control for assessing library quality based on liquid media; anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 60 publications
1
50
1
2
Order By: Relevance
“…The results of this analysis showed that there were small, but acceptable, deviations from the theoretical distributions of randomized bases (Figure ). The average difference between observed and theoretical values across all measurements was 7 ± 6%, similar to the variation observed previously …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this analysis showed that there were small, but acceptable, deviations from the theoretical distributions of randomized bases (Figure ). The average difference between observed and theoretical values across all measurements was 7 ± 6%, similar to the variation observed previously …”
Section: Resultssupporting
confidence: 89%
“…Assembled products were used to transform E. coli BL21‐Gold (DE3) by electroporation. Library diversity was assessed using the “Quick Quality Control” method . This involves Sanger sequencing the pooled plasmids of the library and quantifying the relative abundance of adenine, thymine, guanine, and cytosine in all three positions of a randomized codon.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, for small numbers of saturated codons (~1-3 codons), the near nondegenerate 22c-trick or the fully non-degenrate DC-Anaylzer / MDC-Analyzer used in conjunction with overlap PCR or QuikChange® mutagenesis (section 3.1) are attractive options owing to their simplicity of use and lack of relative expense. Indeed, the financial benefit of employing these methodologies in comparison with NNK/NNS has been examined recently (Acevedo-Rocha, Reetz & Nov, 2015). However, three saturated codons is the maximum exemplified for each of these techniques as described by the inventing authors (Kille et al, 2013;Tang et al, 2012;Tang et al, 2014), presumably because the number of primers becomes Nondegenerate Saturation Mutagenesis 25 unmanageable for higher numbers or saturated positions and also because those primers are specific to individual saturation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Up-front investment in library synthesis is economically advantageous even when considering small libraries (Acevedo-Rocha, 2015). This effect can only be amplified when screening large (>10 9 protein libraries).…”
Section: Discussionmentioning
confidence: 99%
“…Combinatorial approaches such as diand tri-nucleotide block precursors (68,69,74) for oligonucleotide synthesis can further reduce or eliminate redundancy but may be prohibitively expensive for some laboratories. Novel combinatorial strategies are being devised to generate both cost-effective and nondegenerate mutagenic primers and have been assisted by computational efforts (75)(76)(77). Investigators should consider the type or scope of mutations incorporated and the potential forms of bias in each approach when developing selection and evolution strategies for a particular application (74).…”
Section: Combinatorial Libraries and Randomizationmentioning
confidence: 99%